Correlation of Work Motivation, Reward, and Punishment with Compliance Behavior in Using Personal Protective Equipment - Alfi Wardina Faradisa; Tri Martiana (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: PT. X Surabaya is a company engaged in the field of construction services. Construction is an industrial sector which accounts for the highest accident rates in Indonesia. The high number of accidents in companies is a result of employee behaviors, one of which is related to the use of PPE. Based on Activator-Behavior-Consequence (ABC) model, factors that influence worker compliance behavior can be determined. From here, measures to strengthen or weaken the behavior can be proposed. This study aims to analyze the correlation between activator and consequence factors with compliance behavior in using PPE. Method: This study was an analytic observational study with a cross sectional design. This study used sample size by a total population of 32 construction workers at PT. X Surabaya. The variables studied were work motivation, reward, and punishment as independent variables, while the behavior of using PPE as the dependent variable in this study. Data were gathered by collecting company’s secondary data, questionnaires, and observations by using critical behavior checklist instrument. The research analysis used the Spearman correlation statistical test. Results: The Spearman correlation statistical test showed that the relation between work motivation with compliance behavior in using PPE (r = 0.329), reward with compliance behavior in using PPE (r = 0.374), and punishment with compliance behavior in using PPE (r = 0.263) was weak. Conclusion: Work motivation, reward, and punishment had a correlation with compliance behavior in using PPE, but these factors had a weak correlation. There may be other correlated factors in determining compliance behavior in using PPE.Keywords: punishment, reward, work motivation